A Policy Note on Telecommunications Reform in Algeria - Noumba, Paul (World Bank, Washington, D.C., 2013)
By the end of the 1990s, most industrial and many developing countries had liberalized their telecommunications markets to improve service accessibility and affordability for both businesses and households. In contrast, Algeria still managed its telecommunications sector as public property. The Ministry of Post and Telecommunications set the policy, enforced regulation, and was in charge of service provision. The sector suffered from huge supply shortages, the waiting list lengthened, the quality of service deteriorated and unbalanced the overall fiscal situation. In 1999, a new government appointed in the aftermath of President Bouteflika's election decided to change the situation and launched a comprehensive sector reform. Um reviews progress made in implementing this reform, discusses its preliminary impact, and comments on the main lessons learned. The author shows that by restraining arbitrary administrative action during the reform implementation, the government of Algeria laid the foundation for sustainable growth in the telecommunications sector.